Textile subwaste as a thermal insulation building material - Paiva, A. (2012)
This research work is focused on analyzing the potential application of textile subwaste as an alternative building thermal insulation material for double external walls, and in a sustainable perspective. The studied textile subwaste results from the mattress industry and it was briefly characterized as a material. Taking into account that it is necessary to achieve the thermal insulation performance of the proposed technological building solution an alternative expedite experimental setup is also proposed here. It was concluded that using the textile subwaste, a double external wall’s thermal insulation performance may be increased in 33%.